Aerospace series. Connectors, electrical, circular, coupled by threaded ring, fire-resistant or non fire-resistant, operating temperatures - 65 °C to 175 °C continuous, 200 °C continuous, 260 °C peak. Protective cover for plug. Product standard Part 010, (31st January 2015) - British Standards Institution,
No abstract available